Prevalence of and risk factors for minor and major depression among community-dwelling older adults in Taiwan. (10th April 2017) - Wu, Chi-Shin; Yu, Shu-Han; Lee, Chun-Yi; Tseng, Han-Yun; Chiu, Yen-Feng; Hsiung, Chao Agnes
ABSTRACT: Background: This study was conducted to estimate prevalence rates and risk factors for late-life depression in a large nationwide representative sample from Taiwan. Methods: A total of 5, 664, randomly sampled individuals aged ≥55 years were enrolled. Clinically, relevant depressive symptoms were classified using the Center for Epidemiological Studies Depression Scale (CES-D score ≥16), and major depression was confirmed using the Primary Care Evaluation of Mental Disorders. Individuals with clinically relevant depressive symptoms, who did not meet the strict diagnostic criteria for major depression, were considered to have minor depression. Multinomial logistic regression analyses were conducted to identify risk factors for major and minor depression, including socio-demographic characteristics, medical conditions, lifestyle behaviors, social support network, and life events. Results: The prevalence rates of minor and major depression were 3.7% and 1.5%, respectively. Major depression was associated with personal vulnerability factors, such as poor social support, cognitive impairment, comorbid pain conditions, and sleep disturbance. However, minor depression was more likely to be related to adverse life events, including increased burden on families, changes in health status, or relationship problem. Approximately, 20.0% of individuals with major depression received antidepressant treatment. Conclusions: Late-life depression was less prevalent among community-dwelling older adults in Taiwan than among populations in other countries. Our findings may aid the early detection and treatment of late-life depression and provide a basis for future investigations.